2011
DOI: 10.1111/j.1468-1331.2011.03538.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between self‐reported executive performance and psychological characteristics in multiple sclerosis

Abstract: Self-reports of executive performance are generally reliable, but 29% of patients with MS underestimated or overestimated their abilities. It is especially important to identify underestimators as they display underlying psychological problems and dysfunctional coping styles in need of further psychological treatment. Informants are valuable in this respect, but should not be seen as the 'gold standard' to identify cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
4
34
1
2
Order By: Relevance
“…This is partly consistent with previous studies reporting weak relations between subjective and objective measures of cognitive function in MS (6). It is further in agreement with previous studies suggesting that depressed MS patients may underestimate their cognitive performance (11,12).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is partly consistent with previous studies reporting weak relations between subjective and objective measures of cognitive function in MS (6). It is further in agreement with previous studies suggesting that depressed MS patients may underestimate their cognitive performance (11,12).…”
Section: Discussionsupporting
confidence: 93%
“…Earlier findings by Bruce and Arnett (14) partly supported these results as they found that mildly depressed MS patients underestimated their cognitive performance while moderately depressed patients accurately estimated their cognitive performance. Van der Hiele (6) found that nearly 30% of patients with executive problems either underestimated or overestimated their cognitive abilities. Those who underestimated their performance reported more depression, anxiety, and psychosocial stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing interest in self assessment scales understanding the background of disagreement is of increasing importance. It has been subject to research before and possible explaining factors are depression, anxiety and caregiver burden [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…All subjects gave informed consent. More details about the main research project can be found in our recent paper on self-reported executive performance in MS [18].…”
Section: Participantsmentioning
confidence: 99%